Dynamic Modeling and Simulation of a Super-High-Speed Circumferential-Flux Hysteresis Motor. (31st January 2013) - Halvaei Niasar, A.; Zare, M.; Moghbelli, H.
Abstract : There is an interest in super-high-speed motors in industry applications such as gyroscope, micro gas turbines, centrifuge, machine tool spindle drives, and information storage disk drives. This paper presents the dynamic performance characteristics of hysteresis motors using a Matlab/Simulink software. A nonlinear mathematical model based on a d-q axis theory in the rotor reference frame is applied to study the starting and synchronization processes of a hysteresis machine with a circumferential-flux-type rotor. The steady-state and transient responses of the motor to different changes such as the variation in the load torque are provided. The calculation method of the motor parameters in dynamic modeling based on a steady-state model of the motor is presented. The simulation results such as the current, the input power, and power factor are compared with some experimental results in steady-state condition.